2008
DOI: 10.1002/pd.2140
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free DNA in amniotic fluid remains to be attached to HMGA2–implications for noninvasive prenatal diagnosis

Abstract: Our data clearly show that cells of the amniotic fluid strongly overexpress HMGA2 according to their fetal origin. The fact that apparently HMGA2 remains to be attached to cell-free DNA suggests interesting new approaches in noninvasive prenatal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although cffDNA is highly fragmented (100-400 bp), it represents the complete fetal genome and is essentially free of maternal or trophoblastderived DNA. [13][14][15] Several promising reports have demonstrated the feasibility of using cffDNA for array comparative genomic hybridization-based prenatal diagnosis. [16][17][18][19] To date, limited data exist regarding the accuracy and reproducibility of cffDNA as an alternative DNA template for molecular diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cffDNA is highly fragmented (100-400 bp), it represents the complete fetal genome and is essentially free of maternal or trophoblastderived DNA. [13][14][15] Several promising reports have demonstrated the feasibility of using cffDNA for array comparative genomic hybridization-based prenatal diagnosis. [16][17][18][19] To date, limited data exist regarding the accuracy and reproducibility of cffDNA as an alternative DNA template for molecular diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to amniocytes, amniotic fluid (AF) also contains cell‐free fetal DNA (cffDNA). Although cffDNA is highly fragmented (100–400 bp), it represents the complete fetal genome and is essentially free of maternal or trophoblast‐derived DNA . Several promising reports have demonstrated the feasibility of using cffDNA for array comparative genomic hybridization‐based prenatal diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…Winter et al found that high-mobility group protein HMGA2, which is primarily expressed by embryonic and fetal cells, is bound to cffDNA in amniotic fluid. This finding has significance for improving the yield of cffDNA from supernatant via immunoprecipitation techniques [80]. …”
Section: Fetal Nucleic Acids In Amniotic Fluidmentioning
confidence: 99%
“…It has been shown that AF is a rich source of cff DNA . The supernatant of AF contains a high concentration of cff DNA (>17,000 GE/mL) and is a valuable source of pure fetal DNA free of maternal contamination or trophoblast derived nucleic acids . Although fragmented (~100–400 bp), cff DNA and RNA from AF supernatant represent the complete fetal genome, and several studies have shown its successful utilization for array comparative genomic hybridization (aCGH) analysis using bacterial artificial chromosome (BAC) arrays and transcriptomic analysis …”
Section: Introductionmentioning
confidence: 99%